Fruits: nutritious, colourful, yet fragile gifts of nature - Osman, Azizah (Universiti Putra Malaysia Press, 2011)
Fruits, which are consumed because of their excellent taste and health benefits, mainly contribute carbohydrate, dietary fibre, vitamins and minerals to balance the human diet. Fruits have been a part of the human diet since the dawn of history but their nutritional importance has only been recognised in recent times. Commerce in fruits began in the 1980’s when awareness on their nutritional importance has risen. Since then, its demand in the international markets has also increased tremendously. Hence, many tropical countries have moved from small, scattered farms to large commercial fruit plantations. Malaysia went through a series of phases since the inception of the National Agricultural Policy in 1984 to develop its fruit industry to reach its present status- able to be a leading exporter of some tropical fruits. It is not possible to improve the quality of fruits once the fruits harvested but they can be preserved by slowing down the rate of undesirable changes, which leads to a reduction in their quality. Postharvest qualities of fruits are affected by pre-harvest factors, stage of maturity at harvest and postharvest factors. This is due to the fact that there are many physico-chemical changes taking place during growth, maturation, ripening and senescence stages in the life span of the fruit. A range of environmental conditions such as temperature, relative humidity, atmospheric compositions and mechanical injury can influence the rate at which these changes occur in harvested fruits. All these can be manipulated by careful management of the postharvest handling system for maintenance of quality and extension of shelf life of the fruits. Proper postharvest handling practices are essential to reduce postharvest losses and maintain overall quality of fruits after harvest. Human factors such as handling practices and attitudes, and technical aspects such as improper infrastructure and handling techniques could contribute to these losses. Due to change in the life style especially in urban areas, convenient and ready-to-eat fresh-cut fruits, which is also referred to as minimally processed fruits are becoming more popular in the last two decades. However, there are problems associated to it. Hence, studies were conducted to overcome these problems. Apart from the increasing demands for fresh-cut fruits, there is also a trend during the same period of time, where consumers consume fruits not only for its nutritional contents but emphasis is also given to its functional properties. The way forward for the fruit industry globally, including Malaysia, is to develop technology both for whole, intact and minimally processed fruits for shelf-life extension and quality maintenance not only from the perspective of nutritional aspects but also to give emphasis on the stability of the functional properties when they are being subjected to the different postharvest technologies at different stages of the distribution chains (whole, intact fruits) and preparation (minimally processed fruits).